INDICATORS OF GENERAL IMMUNITY IN PATIENTS WITH IATROGENIC MAXILLARY SINUSITIS - Varzhapetian, S.D.; Gulyuk А.G.; Shnaider, S.A.; Strogonova, T.V.; Babenia, H.O.; Reyzvikh, O.E.; Diieva, T.V. (World of Medicine and Biology, 2022)
The dependence of the pathogenesis of chronic maxillary sinusitis on the factors influencing the formation of the maxillary course of the disease was studied according to the indicators of general immunity. The pathogenesis of the drug-induced iatrogenic sinusitis is due not to the nature of dental manipulations, and long-term use of drugs. In other forms of iatrogenic sinusitis of dental origin, the severity of the disease directly depends on the nature and extent of dental intervention. For the drug form, the acute phase of inflammation and the secondary type of immune response are more pronounced in relation to other studied iatrogenic subgroups against the background of low induced activity of immune cells: T-cell parameters (CD 3+, CD56+) – 5.8 %; average CIC – 82.4±4.45 ОU (p